Malnutrion In Patient Cancer - Elio Carmen (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Nutrition is an important part on the implementation of cancer, both in patients who are undergoing therapy, restoration of the therapy, in a State of remission or to prevent a recurrence. Nutritional status in cancer patients is known to correlate with response therapy, prognosis and quality of life. More or less 30-87% of cancer patients experiencing malnutrition before undergoing therapy. The incidence of malnutrition vary depending on the origin of cancer, for example in patients with pancreatic cancer and gaster are experiencing malnutrition to 85%, 66% in lung cancer, and 35% in breast cancer. One of the problems of nutrients that need attention in cancer patients is the kaheksia. The malnutrition common in advance because the nutrition component of the intake not as recommended.